Failure Analysis and Prevention of Square Keyway Shaft Fracture - Kang Jing (Jixie chuandong)
According to three failure cases of shaft fracture on the coal belt conveyor reducer,the fracture surface is analyzed and the finite elements calculation method is used to found the shaft fracture causes.The complex fracture formation and features and its effect on the shaft strength are demonstrated,meanwhile,points for attention when using square keyway are proposed.